Poster Presentations 2017
DOI: 10.1136/bmjspcare-2017-00133.58
|View full text |Cite
|
Sign up to set email alerts
|

P-58 The palliative academic clinical trainees society: description and career outcomes of a novel peer support programme for academic trainees in palliative medicine

Abstract: identified 61 patients who died before being discharged to their PPC. Their clinical notes were obtained and data was collected on modifiable delays. Results Forty-seven complete sets of notes were obtained. The most significant delay was in completing and sending FT paperwork (30/47). Paperwork was not started for 3 patients and incomplete for 7 patients without explanation. Paperwork took 2-4 days to complete for 5 patients, 5-7 days for 12 patients and >8 days for 2 patients.Despite healthcare professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our model reinforces the need for professionals to work collaboratively in EoL care to ensure that the positive, learning experiences outweigh the negative effects of this experiences – particularly in those professionals experiencing this aspect of care for the first time. Peer support within the multi-disciplinary team has been found helpful (Buschbach et al., 2020; Etkind et al., 2017 and it has been found that emotional support and encouraging reflexivity that involves professionals from different disciplines is very helpful (Manning-Jones et al., 2016). This is also important as studies have found that a negative first experience of EoL care can be particularly damaging to a professional’s development (Linane et al., 2019) and that there is a vital importance for members of the EoL care team be supportive of one another (Chan et al., 2016; Harrison et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model reinforces the need for professionals to work collaboratively in EoL care to ensure that the positive, learning experiences outweigh the negative effects of this experiences – particularly in those professionals experiencing this aspect of care for the first time. Peer support within the multi-disciplinary team has been found helpful (Buschbach et al., 2020; Etkind et al., 2017 and it has been found that emotional support and encouraging reflexivity that involves professionals from different disciplines is very helpful (Manning-Jones et al., 2016). This is also important as studies have found that a negative first experience of EoL care can be particularly damaging to a professional’s development (Linane et al., 2019) and that there is a vital importance for members of the EoL care team be supportive of one another (Chan et al., 2016; Harrison et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the paucity of research that explores the first-time experience of death in hospital setting, our study shows how different HPs perceive and cope with the death of a patient, mainly when this experience occurs with non-oncologic patients. EoL care is increasingly multi-disciplinary and it has been found that this increases its effectiveness (Schneiter et al, 2019) and it is important that the professionals involved understand how EoL experiences can have a psychological effect on their colleagues (Buschbach et al 2020;Etkind et al, 2017). It is also important that the multi-disciplinary team in EoL care learn to reflect on the psycho-social aspects of EoL care and use these in a way that improves the work of the team and also -crucially -enables better peer support, which is vital for stress reduction and burnout among HPs in this line of work (Harrison et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a known disparity of research opportunities for the specialty. There are proportionally four times fewer academic trainees in palliative medicine than oncology 12…”
Section: Introductionmentioning
confidence: 99%